2011
DOI: 10.1007/s11102-011-0339-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cabergoline and bromocriptine on the risk of valvular heart disease in patients with prolactinomas

Abstract: Therapy with dopamine agonists has been associated with valvular heart disease (VHD) in Parkinson's disease, raising concern about the safety of these drugs. In hyperprolactinemic patients, the studies have mainly focused on the cardiac effects of cabergoline (CBG), with little information on bromocriptine (BRC). The aim of the present study was to evaluate the prevalence of VHD in patients with prolactinomas treated with CBG and BRC. The CBG group consisted of 51 patients (37 female; age 42.3 ± 13.5 years) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
2
35
2
5
Order By: Relevance
“…Results from 15 observational studies investigating the risk of fibrotic valvulopathy in hyperprolactinemic patients treated with CAB have been published to date (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27). Two of them (15,20) have shown no relevant findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from 15 observational studies investigating the risk of fibrotic valvulopathy in hyperprolactinemic patients treated with CAB have been published to date (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27). Two of them (15,20) have shown no relevant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (16,18,21,24) have demonstrated an increased prevalence of non-clinically relevant valve regurgitations, including mild tricuspid regurgitation (16,21,24), pulmonic insufficiency (16), or enlarged mitral tenting area (18). Ten trials (13,14,17,18,19,22,23,25,26,27) have reported a variable prevalence, ranging from 2% (25) to 54% (13), of relevant valvulopathy including moderate-to-severe mitral or tricuspid insufficiency and mild aortic regurgitation, with the latter being observed only in two investigations (22,24). Overall, a median CRVD rate of w4% has been reported in hyperprolactinemic patients receiving treatment with CAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cabergoline use in the endocrine setting, they did find a trend to develop mild to moderate valve regurgitation. In their analysis, they included seven studies [13,24,26,31,32,39,40] comparing data of 444 treated cases versus 954 controls. They conclude that although globally safe, a periodic ultrasound assessment should not be avoided even if cabergoline dose is low.…”
Section: Discussionmentioning
confidence: 99%
“…Published data on the potential profibrotic effect of bromocriptine, a partial 5HT 2b agonist, are exclusively limited (19). Although there are numerous case reports in the literature, only a few studies have been dedicated to this topic (13,17,20,21). As drug-induced valvulopathy in Parkinsonian patients has been shown to be a cumulative dosedependent process, for potentially at-risk groups, not only patients receiving high daily doses, but also those on low-dose long-term treatment, such as patients with invasive macroprolactinomas who are often on lifelong therapy, should be considered.…”
Section: Introductionmentioning
confidence: 99%